ANALISIS FRAMING EPISODE “MEREKA RAMAI-RAMAI MENGGUGAT KPK” PADA PROGRAM REALITAS METRO TV - Z I, Shabrina; Nasution, Belli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Early 2015 in Indonesia is dominated by the feud between the Corruption Eradication Commission (KPK) and the Indonesian National Police (INP). Realitas is an investigative news program in Metro TV that review more into the news. Realitas review the feud between the KPK and the National Police in the episode